Single cell transcriptomics reveals lineage trajectory of retinal ganglion cells in wild-type and Atoh7-null retinas - Fuguo Wu (Nature Portfolio, 2021)
Atoh7 is essential for retinal ganglion cell (RGC) genesis. Here the authors perform scRNAseq on embryonic mouse retina and conclude that Atoh7 defines a transitional state and that other factors also participate in establishing the RGC lineage.